Os cursos semipresenciais como oferta de escolarização: ajustes, desajustes e reajustes em relação as necessidades do público jovem e adulto - Farias, Humberto Vieira (2022)
Every Brazilian citizen has the constitutional right to access school education. With a view to exercising this right, a contingent of young people, adults and the elderly searches for public education systems across the country that provide schooling via face-to-face courses. However, in some systems, it is possible to enroll in blended courses, which are the focus of this thesis work, whose objective was to identify, based on academic research, contributions that justify the maintenance of this schooling offer as it adjusts to the needs of the public. young and adult. This is a systematic review of academic productions at postgraduate level that date between the years 2000 and 2020, based on the methodological procedures of bibliographical research, presented by Gil (2002, 2008), Marconi and Lakatos (1992) and Salvador (1970). Based on the theoretical conception that guides this research, on the theoretical support of authors who discuss EJA in Brazil, on the data available at INEP and on information present in the fifty-four selected studies, it was possible to reconstruct the historical trajectory, discuss the organization of EJA blended courses, organize information, perform interpretations, make inferences, analyze the contributions of each research regarding EJA blended courses. The results demonstrate that there are situations that represent adjustments of the offer in relation to the public of the modality and that, despite the apparent mismatches observed, these are not related to the blended didactic-pedagogical mediation, but with situations involving the teaching performance, the absence of material adequate didactics, the lack of continuing education and the possible exclusion from the offer in relation to education policies, among others. Finally, the research also indicated that in the spaces where blended EJA courses are offered, there are readjustments that bring this offer model even closer to the needs of students, adjustments developed by committed professionals who believe in the possibility of moving forward, whether in promoting dialogue, valuing the presence of students, using technology, improving teaching resources, assessments and teachers' practices. Therefore, the results confirm the thesis that blended courses constitute a schooling offer adjusted to the reality of a portion of the young and adult public, due to several factors, especially social ones, which made access, permanence or completion of schooling unfeasible. basis, through other offer models.